Diazonium chemistry surface treatment of piezoelectric polyhydroxybutyrate scaffolds for enhanced osteoblastic cell growth. (September 2020) - Chernozem, R.V.; Guselnikova, O.; Surmeneva, M.A.; Postnikov, P.S.; Abalymov, A.A.; Parakhonskiy, B.V.; De Roo, N.; Depla, D.; Skirtach, A.G.; Surmenev, R.A.
Highlights: 3D fibrous scaffolds were modified by 3, 4-dicarboxybenzenediazonium tosylate (ADT-(COOH)2 ). diazonium modification allowed to preserve a pronounced piezoelectric response. PHB scaffolds demonstrated reduced d33 value from 2.5 ± 0.3 pCN −1 to 2.1 ± 0.4 pCN −1 . surface electric potential decreased from 510±56 mV to 458±25 mV after surface treatment. cell density increased on the surface of ADT-(COOH)2 -treated fibers. Abstract: Biodegradable piezoelectric 3D polymer scaffolds attract great attention due to possibilities to mimic the functional and mechanical properties of the extracellular matrix, avoiding secondary surgery, and electrically stimulated tissue repair. However, the preservation of piezoelectric response and improvement of wettability of hydrophobic fibrous polymer scaffolds, limiting their application in tissue engineering and regenerative medicine, is a challenge. Here, a facile and mild approach is presented to improve wettability and cell spreading on the surface of piezoelectric polyhydroxybutyrate (PHB) and non-piezoelectric polycaprolactone (PCL) scaffolds. The surface of electrospun 3D fibrous scaffolds was modified by 3, 4-dicarboxybenzenediazonium tosylate (ADT-(COOH)2 ) via photo-induced formation of aryl radicals under ultraviolet irradiation. According to scanning electron microscopy and x-ray diffraction analyses, the intrinsic structure of 3D scaffolds remains unaffected after the treatment. Meanwhile, the attachment of hydrophilic 3, 4-dicaboxyphenyl groups to the surface led to an apparent decrease of the water contact angle from 127±4° to 82±1° for PCL and from 126±4° to 78±2° for PHB, i.e. resulting in the change of the scaffold's wettability from hydrophobic to hydrophilic. Furthermore, no aging of the improved wetting was observed for 21 days. The diazonium modification allows to preserve a pronounced piezoelectric response, since PHB scaffolds demonstrate a slightly reduced effective d33 from 2.5 ± 0.3 pCN −1 to 2.1 ± 0.4 pCN −1 and surface electric potential from 510±56 mV to 458±25 mV after surface treatment. At the same time, after C6 H3 -(COOH)2 grafting, osteoblastic cells were well-spread along the PCL and PHB fibrous scaffolds. Moreover, after 7 days of incubation, the cell density is increased on the surface of ADT-(COOH)2 -treated fibers in comparison to that on pristine ones, while cells formed a distinct osteoblastic network. Graphical abstract: Image, graphical abstract